Kissing lips Humahalik na mga labi - Rogado, Marites R. (Lampara books, 2013)
"Kissing lips, lips made of paper through origami, tells the story of young Ada who becomes witness to a misunderstanding between her mama and papa who end up not speaking to each other. Find out in this story how Ada prompts her parents to be in good terms with each other again, and how a pastime can help during such an incident."